«Академічна доброчесність» в Україні: місце в освітньому процесі та законодовче регулювання - Куліш, А. М.; Kulish, A. M.; Дуліба, Є. В.; Duliba, Ye. V.; Миргород-Карпова, В. В.; Myrhorod-Karpova, V. V.; Аврамова, О. Є.; Avramova, O. Y.; ORCID: http://orcid.org/0000-0002-1941-9894 (Наукові записки [Центральноукр. держ. пед. ун-ту імені Володимира Винниченка]. Сер.: Право. – 2022. – Вип. 12. – С. 258-265, 2022)
Розглянуто основи утворення академічної доброчесності на міжнародній арені та в національному просторі. Вказано, що освітній процес є динамічним, оскільки наповнений постійними реформами, модернізаціями, удосконаленнями, а також вступом нових талановитих і здібних студентів. Разом із нововведеннями щодо освітнього процесу з’являються нові виклики та проблеми в отриманні якісної освіти. Все більше студентів знецінюють важливість якості освіти та використовують механізми для полегшення виконання наукових робіт. Такі механізми у національному законодавстві визначаються як «академічна недоброчесність». Розглянуто особливості впровадження академічної доброчесності у XX столітті та проаналізовано основоположні поняття у цій сфері. Акцентовано увагу на проблемах та передумовах порушення доброчесності студентами. За результатами опитування, встановлено, що вмотивованість викладача дуже впливає на бажання студентів навчатись. А завищений обсяг наукових робіт, та вимоги, які не відповідають інтелектуальному рівню відповідно до року навчання, спонукає використовувати плагіат. Наголошено, що освітні заклади повинні контролювати це питання. Також необхідно донести до студентів ту думку, що у випадку недотримання принципів академічної доброчесності розвиток науки постає під загрозою, адже саме молоді вчені є каталізатором змін.

The article is devoted to the foundations of the formation of academic integrity in the international arena and in the national space. It is indicated that education is a priority for any modern state, because the future of Ukraine depends on the graduates of educational institutions. The educational process is dynamic, as it is filled with constant reforms, modernizations, improvements, as well as the admission of new talented and capable students. Along with innovations in the educational process, new challenges and problems in obtaining quality education appear. More and more students underestimate the importance of quality education and use mechanisms to facilitate the performance of scientific works. The article emphasizes that such mechanisms are defined as "academic dishonesty" in national legislation. The peculiarities of the implementation of academic integrity in the 20th century were considered and the fundamental concepts in this field were analyzed. Attention is focused on the problems and prerequisites of violation of integrity by students. In the article, special attention is paid to the question of the prerequisites for the students' desire not to observe the rules of academic integrity. A survey was conducted among students regarding the causes of academic dishonesty. As a result, it was established that the teacher's motivation greatly affects the students' desire to learn. Also, according to the results of the survey, it was determined that the inflated volume of scientific works, and requirements that do not correspond to the intellectual level according to the year of study, encourages the use of plagiarism. It was concluded that educational institutions should control this issue. It is also necessary to convey to students the idea that in case of non-compliance with the principles of academic integrity, the development of science is in danger, because it is young scientists who are the catalyst for change.

Рассмотрены основы образования академической добродетели на международной арене и в национальном пространстве. Указано, что образовательный процесс динамичен, поскольку наполнен постоянными реформами, модернизациями, усовершенствованиями, а также вступлением новых талантливых и способных студентов. Вместе с новшествами в образовательном процессе появляются новые вызовы и проблемы в получении качественного образования. Все большее количество студентов обесценивают важность качества образования и используют механизмы для облегчения выполнения научных работ. Такие механизмы в национальном законодательстве определяются как академическая недоброчестность. Рассмотрены особенности внедрения академической добродетели в XX веке и проанализированы основополагающие понятия в этой сфере. Акцентировано внимание на проблемах и предпосылках нарушения добродетели студентами. По результатам опроса установлено, что мотивированность преподавателя оказывает большое влияние на желание студентов учиться. А завышенный объем научных работ и требования, не отвечающие интеллектуальному уровню в соответствии с годом обучения, побуждает использовать плагиат. Отмечено, что образовательные учреждения должны контролировать этот вопрос. Также необходимо донести до студентов то мнение, что в случае несоблюдения принципов академической добродетели, развитие науки возникает под угрозой, ведь именно молодые ученые являются катализатором изменений.
The methodological basis of the functioning of the concept of “academic integrity” in Ukraine: administrative and legal analysis
Куліш, А. М. «Академічна доброчесність» в Україні: місце в освітньому процесі та законодовче регулювання / Куліш Анатолій Миколайович, Дуліба Євгенія Володимирівна, Миргород-Карпова Валерія Валеріївна, Аврамова Ольга Євгенівна // Наукові записки [Центральноукр. держ. пед. ун-ту імені Володимира Винниченка]. Сер.: Право. – 2022. – Вип. 12. – С. 258-265. - DOI: https://doi.org/10.36550/2522-9230-2022-12-258-265.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; академічна доброчесність; academic integrity; академическая добродетель; академічна недоброчесність; academic dishonesty; академическое недоброчестие; освітній процес; educational process; образовательный процесс; заклади вищої освіти; institutions of higher education; заведения высшего образования; міжнародні норми; international norms; международные нормы; академічний плагіат; academic plagiarism; академический плагиат; законодавче регулювання; legislative regulation; законодательное регулирование